Effect of treadmill training combined with ankle weight on balance in spastic cerebral palsied children: A randomized controlled trial - Wagdy, Eman; Adel Ahmed, Angham M.; Mohammed Hassan, Manal; Ahmed Kamal, Ola; Aziz, Marwa A.; Mouhamed, Hanady A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to examine the impact of treadmill training combined with ankle weights on balance and dorsiflexor muscle strength in children with spastic hemiparetic cerebral palsy (CP). This clinical, randomized trial included forty boys and girls suffering from spastic hemiparetic cerebral palsy, ranging in age from 6 to 9 years old. They were split into two equal groups (control group = 20, study group = 20). Both groups received a program of physiotherapy in addition to treadmill exercise, while the study group also received ankle weights for eight weeks. The Biodex stability system was employed to evaluate stability indices, including the overall stability index (OASI), anteroposterior stability index (APSI), and mediolateral stability index (MLSI). Functional balance was measured using the Pediatric Balance Scale (PBS). A Lafayette manual muscle tester (MMT) was used to record the peak force of ankle dorsiflexor muscle strength for both groups, pre- and post-therapy. Post-therapy results showed a significant decrease in all stability indices at stability levels 8 and 4, and a significant increase was observed in functional balance and ankle dorsiflexor muscle strength in both groups (p<0.05). The study group showed a more significant improvement in all outcome measures after therapy than the control group (p<0.05). The program of physiotherapy, treadmill training, and ankle weights was effective in improving balance and dorsiflexor muscle strength among children with spastic hemiparetic cerebral palsy, with ankle weights contributing to greater progress.